A Longitudinal Quasi-Experimental Study of Violence and Disorder Impacts of Urban CCTV Camera Clusters. (June 2019) - Ratcliffe, Jerry H.; Groff, Elizabeth R.
Methodological challenges have hampered a number of previous studies into the crime reduction effectiveness of closed-circuit television (CCTV) surveillance systems. These have included the use of arbitrary fixed distances to represent estimated camera deterrence areas and a lack of control for camera sites with overlapping surveillance areas. The current article overcomes the first of these challenges by using camera view areas individually constructed by researchers viewing and manipulating cameras to determine precise camera viewsheds. The second challenge is addressed by grouping cameras into clusters of combined viewshed areas. The longitudinal crime and disorder reduction effectiveness of these clusters of overlapping CCTV cameras is tested in Philadelphia, PA. Multilevel mixed-effects models with time-varying covariates and measures from a noncomparable control area are applied to 10 years of crime data (2003–2012) within the viewsheds of 86 CCTV cameras grouped into 13 clusters. Models applied across violent street felonies and disorder incidents find no significant impact associated with the introduction of CCTV surveillance. Potential reasons for this are discussed.